A systematic meta-analysis and meta-synthesis of the impact of service-learning programs on university students' empathy. (November 2022) - Gordon, Chloe S.; Pink, M.A.; Rosing, H.; Mizzi, S.
Abstract: Higher education institutions seek not only to prepare students for their chosen profession, but also to develop graduates that are civic minded and make a positive social impact. The purpose of this paper is to review the literature on whether participation in service-learning leads to students reporting increased empathy. The study also examines the features within a service-learning placement that contribute to development of empathy. The review followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement. The authors searched Scopus, ERIC (EBSCOhost), PsycInfo, CINAHL, Web of Science, Medline Complete, Google Scholar and specific service-learning journals not indexed in major databases for studies published before Nov 23, 2020 that met the Bringle and Hatcher (1995) definition of service-learning and measured change in, or development of, empathy. Of 662 records identified, 35 met the inclusion criteria and were included in the review. Overall, across the 14 studies included in the meta-analysis, there was a significant small effect for increase in empathy for those who participated in service-learning compared to those who did not ( g = 0.261) and from pre to post service-learning ( g = 0.176). Across the 21 qualitative studies, the main feature which appeared to contribute to the development of students' empathy was direct interactions with the community. This paper provides insight into the efficacy of service-learning as a pedagogy and contributes to our understanding of the educational value of service-learning for universities. We conclude with avenues for future research and implications for practice. Highlights: We report a meta-analysis on service-learning and students' empathy. Study shows a significant small effect for increase in empathy. A meta-synthesis highlights factors that contribute to empathy development. Direct interactions with community the main factor that increases empathy. Gaps in the literature are highlighted and implications for practice discussed.